Policy Analysis of The National Capital from An Economic-Political Perspective - Emrialdi, Pebriansyah; Valentina, Tengku Rika; Putri, Indah Adi (STIA Adabiah, 2024)
Indonesia's plan to relocate its capital from Jakarta to East Kalimantan is driven by various socio-economic and environmental challenges in Jakarta, including overcrowding, economic disparity, water scarcity, and environmental degradation. The decision has faced criticism for its potential financial burden amidst the COVID-19 pandemic recovery efforts and concerns over legal and managerial complexities. Despite the strategic benefits of reduced congestion and disaster risk in Kalimantan, issues such as social integration, security threats, and the need for substantial funding remain pivotal in determining the project's success. This paper employs a qualitative descriptive approach, integrating academic literature and expert opinions, to analyze the economic-political implications of the capital relocation amid public resistance and government challenges.